Inventory of Chili Pests and Diseases in Kabandungan Sub-District, Sukabumi Regency - R. Arif Malik Ramadhan; Dhea Nurul Amalia; Indra Permana; Panji Rahmatullah (JERAMI : Indonesian Journal of Crop Science, 2023)
The decline in chili commodity production is influenced by various factors, including climate anomalies, less than optimal cultivation techniques, decreasing land quality, and pest attacks. Kabandungan District, as one of the chili production centers, can be used as a reference for studying the presence and intensity of chili pest attacks in general. Information about pest attacks can be used as a basis for control that can be applied in any location with similar characteristics. This research was conducted in Kabandungan District, Sukabumi Regency, West Java Province, Indonesia. This research was carried out from November 2021 to March 2022. The number of chili plants observed was 930 plants which were divided into 61 observation points spread across 6 villages, including Cianaga, Cihamerang, Cipeuteuy, Kabandungan, Mekarjaya, and Tugubandung Villages. The chili plants observed consisted of the local variety of cayenne pepper (CMR), cayenne red chili (CMR), curly red chili (CMK) variety TM 999, Darmais F1 large red chili (CMB), curly red chili (CMK), and chili curly red (CMK) OR Twist 42. The results of the study stated that the incidence of pest attacks was dominated by S. Litura attacks 26.40%, and Colletotrichum capsici 25.60% in the vegetative phase, as well as S. Litura 27.21%, and Gemini Virus 47.35% in the generative phase. S. litura attacks are reported to dominate all villages in Kabandungan District, while Mekarjaya Village is dominated by mites.